Implementation Implementation Of Multikultural Education In Forming The Moral Knowing Of Drugs Administrates In Padepokan Gema Qolbu Prigen - muhammad abdullah; Muslikhah Indah Utari (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
This article aims to describe how the implementation of multikultural education is an alternative in rehabilitating drug addicts by taking preventive actions in the form of multikultural insight that can form moral knowing, as well as how effective the implementation of multikultural education is in shaping the moral knowing of drug addicts. Awareness of the use of illegal drugs is still rampant in various regions in Indonesia. The various cases of criminal acts have become a discourse that will not stop when discussed. Among the forms of preventive action against addicts is to provide insight into multikultural education. This will be able to shape the moral knowing of addicts to be even better. The results of the study concluded that the implementation of multikultural education in shaping the moral knowing of drug addicts in Gema Qolbu Padepokan Ketanireng Prigen Pasuruan. In general, it aims to provide knowledge about preventive drug actions so that drug addicts can become better human beings in society.